Efficient formal synthesis of (S)-dapoxetine from enantiopure 3-hydroxy azetidin-2-one - Chincholkar, Pinak M.; Kale, Ajaykumar S.; Gumaste, Vikas K.; Deshmukh, Abdul Rakeeb A. S. (Tetrahedron, 2009)
An efficient formal synthesis of S-(+) dapoxetine starting from 3-hydroxy azetidin-2-one is described. The intermediate (S)-3-(dimethyl amino)-3-phenylpropan-1-ol was synthesized in enantiopure form starting with 3-hydroxy azetidin-2-one in seven steps. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Azetidin 2 ones; beta-Lactams; Enantioselective synthesis; reduction; Staudinger reaction

Enantioselective total synthesis of (2S,3R,4R)-D-xylo-phytosphingosine from substituted azetidin-2-one - Pandey, Ganesh; Tiwari, Dharmendra Kumar (Tetrahedron Letters, 2009)
Enantiomerically pure (2S,3R,4R)-D-xylo phytosphingosine is synthesized in 36% overall yield in seven steps from known beta-lactam (8) derived from D-mannitol triacetonide. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: beta-lactam; Enantioselective synthesis; Sphingosine; Wittig reaction

N-heterocyclic carbene (NHC)-catalyzed transformations for the synthesis of heterocycles - Das, Tamal Kanti; Biju, Akkattu T. (Progress in Heterocyclic Chemistry, 2020)
N-heterocyclic carbene (NHC)-based organocatalysis has been widely used for unconventional access to various target molecules. The use of chiral NHCs in the process results in the enantioselective synthesis of various heterocycles. The underlying principle of many of the NHC-catalyzed reactions is the remarkable ability of NHCs to reverse the normal mode of reactivity of aldehydes (umpolung). NHCs can catalyze transformations proceeding via the umpolung or nonumpolung mode for the synthesis of various functionalized molecules. The recent advances in the application of NHCs for the synthesis of various heterocyclic compounds are highlighted in this chapter.
Keywords: aldehyde umpolung; Aldimine umpolung; benzoin reaction; Breslow intermediates; Enantioselective synthesis; Heterocyclic synthesis; N-Heterocyclic carbene; Stetter reaction